Escherichia coli diarrhea: a small hospital outbreak among infants caused by serotype O55:B5 - Akman, Muvaffak (The Turkish Journal of Pediatrics, 1961)
The first report of an outbreak of enteropathogenic E. coli diarrhea in Turkey is presented. Methods used in the isolation and treatment are discussed.